2019
DOI: 10.1111/coa.13366
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term quality of life and sensory impact of great auricular nerve preservation in parotid surgery as measured with the Parotidectomy Outcome Inventory‐8

Abstract: Objectives: This study aimed to evaluate sensory dysfunction resulting from great auricular nerve (GAN) sacrifice versus preservation in parotid surgery for benign lesions and its imact on long-term health-related quality of life (QOL). Design: Retrospective.Setting/main outcome measures: Participants were divided into two groups (GAN and non-GAN), and both short-term (two postoperative weeks) and long-term (at least 5 years) QOL were assessed. The second item of the Parotidectomy Outcome Inventory-8 (POI-8) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 17 publications
(31 reference statements)
4
15
0
Order By: Relevance
“…reported that GAN preservation did significantly improve sensation in short-but not in long-term, nor did it increase QOL in long term when compared to GAN sacrifice [13]. Based on the observation period of 12-16 years after parotidectomy, we could show that hypoesthesia significantly improved over the years (p < 0.001) but still remains without limiting patients in QoL, a clinically relevant finding here.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…reported that GAN preservation did significantly improve sensation in short-but not in long-term, nor did it increase QOL in long term when compared to GAN sacrifice [13]. Based on the observation period of 12-16 years after parotidectomy, we could show that hypoesthesia significantly improved over the years (p < 0.001) but still remains without limiting patients in QoL, a clinically relevant finding here.…”
Section: Discussionsupporting
confidence: 64%
“…Consequently, patients should be preoperatively informed about the possible prolonged or permanent hypoesthesia. According to data of Bulut et al [13], we only found a positive association between intraoperative preservation of the GAN and improved hypoesthesia in the ST-cohort (p = 0.028), not in the LT-cohort. Finally, we can conclude that patients seem to adapt to the postoperative functional impairment over time and focus less on the reduced ability to feel temperature and pain on the facial skin over the parotid gland and auricle.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations